Synthesis of Glutathione Modified CdSe Quantum Dots and Its Application in Determination of Trace Hg2+ Ions - Wu, Huacheng; Wang*, Jiangying; Zhang, Jingji; Wang, Lejian; Jia, Xuanrui; He, Mingming; Wang, Chongyuan (Asian Journal of Chemistry, 2014)
The water-soluble glutathione (GSH) modified CdSe quantum dots (QDs) were prepared. Results show that the optimum NaBH4:Se:(Cd2+): glutathione molar ratio is obtained to be 3:1:3:9. Meanwhile, the glutathione modified CdSe quantum dots synthesized by the optimum process have a single face centered cubic phase. It is found that the fluorescence quenching occurred as Hg2+ ions interact with glutathione modified CdSe quantum dots. Hg2+ ions can be determined in the concentration range of 0.3-15 μg/L, which is proposed to determine the trace quantities of Hg2+ ions as fluorescence probe.